Is disability associated with range of motion, pain and mental health-related quality of life in subjects with frozen shoulder? A cross-sectional study. - Poser, Antonio; Brindisino, Fabrizio; Lot, Sebastiano; Andriesse, Arianna; Rossi, Alex; Feller, Daniel; Guerra, Germano; Venturin, Davide (Physiotherapy Theory & Practice, 2025)
Introduction: While the impact of physical impairments on disability is widely acknowledged, recent literature suggests an association between health-related, social, and quality of life aspects, mental distress and unfavorable outcomes in subjects with Frozen Shoulder (FS). Objective: To identify the main contributors to disability among external rotation (ER0°) and flexion (FL) passive Range of Motion (ROM) restrictions, pain and mental health-related quality of life domains in subjects with FS. Methods: The association of the Disability of the Arm, Hand, and Shoulder (DASH) scale (dependent variable) with passive ROM in ER0° and FL, the Shoulder Pain and Disability Index-Pain subscore (SPADI-pain), and the Health Survey Short Form (SF-36) (independent variables) was investigated. Multivariable linear regression including all the independent variables and adjusted for potential confounders was performed. Results: A total of 123 subjects were included. The model showed SPADI-pain (standardized coefficient = 8.83, 95% CI 6.74 to 10.92), passive FL (standardized coefficient = −3.34, 95% CI −5.65 to −1.02) and SF-36 Vitality (standardized coefficient = −3.43, 95% CI −6.45 to −0.41) significantly associated with disability. Conclusions: Disability emerged as a multidimensional burden, influenced by pain, mental, and ROM impairments. These indicators suggest a comprehensive approach to individuals, enhancing overall well-being, feeling of being understood and supported.